2016
DOI: 10.1080/00207411.2016.1204822
|View full text |Cite
|
Sign up to set email alerts
|

Changing Minds: The Psycho-Pathologization of Trans People

Abstract: The concepts of psychiatric diagnosis and gender are both contested, and they are at their most controversial where they intersect around the diagnosis of trans and gender variant people as mentally disordered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Co-occurring psychiatric disorders in gender diverse populations are unlikely to be simply related to the person's gender identity, and may instead reflect the response of the individual's familial and social environment to that identity and its expression (Vrouenraets et al ., 2015). It has been suggested that cisgender populations under the same incessant exposure to psychological stressors would in all likelihood experience comparable of rates of depression and anxiety as trans populations (Inch, 2016). Higher rates of anxiety among transgender adult populations have also been reported, and have been attributed to low self-esteem and poor interpersonal functioning (Bouman et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Co-occurring psychiatric disorders in gender diverse populations are unlikely to be simply related to the person's gender identity, and may instead reflect the response of the individual's familial and social environment to that identity and its expression (Vrouenraets et al ., 2015). It has been suggested that cisgender populations under the same incessant exposure to psychological stressors would in all likelihood experience comparable of rates of depression and anxiety as trans populations (Inch, 2016). Higher rates of anxiety among transgender adult populations have also been reported, and have been attributed to low self-esteem and poor interpersonal functioning (Bouman et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The construction of lesbian women and gay men as sexual deviants has a long history (Conrad, 1992;Gonsiorek, 1982;Minton, 2002) and so this is not a new motif in the de-legitimization of sexual and gender minorities. Similarly, the pathologization of transgender people is well-established through the American Psychiatric Association's (2013) mental disorder category of 'gender dysphoria' and in popular representations (Inch, 2016). In this sense and at least at some level, deviance is characterized as an intrinsic component of lesbian, gay, bisexual and transgender identities.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as Minerva notes, in Brazil free cosmetic surgery is given to the poor in order to enhance their well-being and/or social and economic prospects-rather than to mitigate some harm-and in most European countries cosmetic surgery for physical features that are merely non-average-rather than associated with any medical harm-is provided by public health systems. [45] (p187) Similarly, according to Inch [5] , fertility treatment and breast reconstruction following removal of tumours 'is not necessarily offered due to an illness or a disorder; it is offered in order to improve one's quality of life and psychological wellbeing'(p200-201). Living with integrity enhances our general well-being.…”
Section: IVmentioning
confidence: 99%